Src kinase function controls progenitor cell pools during regeneration and tumor onset in the Drosophila intestine - Kohlmaier, Alexander; Fassnacht, C.; Jin, Yinhua; Reuter, H.; Begum, Jamila; Dutta, Devanjali; Edgar, Bruce (Oncogene, 2015)
Src non-receptor kinases have been implicated in events late in tumor progression. Here, we study the role of Src kinases in the Drosophila intestinal stem cell (ISC) lineage, during tissue homeostasis and tumor onset.